ASPEK HUKUM TERHADAP TINDAK PIDANA PENCUCIAN UANG DENGAN MODUS SMURFING - Faiz, Agil; Yusrizal, Yusrizal; Iskandar, Hadi (Fakultas Hukum Universitas Malikussaleh, 2024)
The objective of this study is to explore the legal dimensions of the criminal offense of money laundering, specifically focusing on the smurfing technique. Additionally, it seeks to examine the evidentiary framework applicable to the crime of money laundering as defined by Act No. 8 of 2010 concerning the Penal Procedure for Money Laundering. The advancement of technology has introduced various innovative methods in the prosecution of money laundering, one of which is the smurfing technique. This method involves the placement of illicitly obtained funds into the financial system by dividing the money into smaller sums and depositing them into bank accounts to evade detection. The concept of smurfing gained prominence following Judgment No. 62/Pid.Sus/2021/PN Jkt.Utr, which referenced